LC-MS Quantification of Site-Specific Phosphorylation Degree by Stable-Isotope Dimethyl Labeling Coupled with Phosphatase Dephosphorylation - Sin-Hong Chen (Molecules, 2020)
Protein phosphorylation is a crucial post-translational modification that plays an important role in the regulation of cellular signaling processes. Site-specific quantitation of phosphorylation levels can help decipher the physiological functions of phosphorylation modifications under diverse physiological statuses. However, quantitative analysis of protein phosphorylation degrees is still a challenging task due to its dynamic nature and the lack of an internal standard simultaneously available for the samples differently prepared for various phosphorylation extents. In this study, stable-isotope dimethyl labeling coupled with phosphatase dephosphorylation (DM + deP) was tried to determine the site-specific degrees of phosphorylation in proteins. Firstly, quantitation accuracy of the (DM + deP) approach was confirmed using synthetic peptides of various simulated phosphorylation degrees. Afterwards, it was applied to evaluate the phosphorylation stoichiometry of milk caseins. The phosphorylation degree of Ser130 on α-S1-casein was also validated by absolute quantification with the corresponding synthetic phosphorylated and nonphosphorylated peptides under a selected reaction monitoring (SRM) mode. Moreover, this (DM + deP) method was used to detect the phosphorylation degree change of Ser82 on the Hsp27 protein of HepG2 cells caused by tert-butyl hydroperoxide (t-BHP) treatment. The results showed that the absolute phosphorylation degree obtained from the (DM + deP) approach was comparable with the relative quantitation resulting from stable-isotope dimethyl labeling coupled with TiO2 enrichment. This study suggested that the (DM + deP) approach is promising for absolute quantification of site-specific degrees of phosphorylation in proteins, and it may provide more convincing information than the relative quantification method.